Literature's social lives: a socio-institutional history of literary value - Leypoldt, Günter (Oxford University Press, 2025)
'Literature's Social Lives' situates itself within an emerging field of a sociologically attuned literary criticism, which combines ethnographic interest in the aesthetics of literary experience with a curiosity about how literature gains cultural relevance and institutional authority. In this groundbreaking study, Günter Leypoldt argues that ever-rising turnover of books between 1800 and 2000 expanded the commercial literary marketplace, yet by inverse subsidy simultaneously stabilized literature's market-sheltered support systems.
Includes bibliographical references and index. - Description based on online resource and publisher information; title from PDF title page (viewed on September 15, 2025)